Communal Sharing as the Foundation of Solidarity Action in Youth Organization - Jayanti, Melani; Minza, Wenty Marina; Nurdiyanto, F A (Faculty of Psychology, Universitas Gadjah Mada, 2024)
Solidarity is a theme frequently discussed to explain social phenomena linked to social concerns and cohesion. It is also a commonly discussed topic in news and research works, especially during crises. Studies about solidarity have elaborated on forms of solidarity action, but only a few discuss the process of solidarity and the dynamics of intragroup relationships. Therefore, this study aimed to explore the patterns and roles of intragroup relationships in the solidarity actions of youth organizations, using a qualitative case study approach. The study involved seven young people (4 men, 3 women) from the Kanal Muda Community, with the consideration of the representativeness of the group’s elements. The data analysis method employed was thematic analysis, considering Fiske’s lens in building the logic of the findings in social relationships. This study found that the communal sharing relationship is the main foundation of solidarity action and enables equal relationships and cooperation within the community. This study attempts to contribute to the literature on the intragroup relationship and its relevance in solidarity action. Communal sharing can also influence the formation of values, norms, working methods, and decision-making in the group.